Gambaran perilaku ibu dan sanitasi lingkungan terhadap kejadian diare pada balita di desa Banyubiru Kecamatan Negara Kabupaten Jembrana Bali 2014 - I Made Yudi Mahardika (Intisari Sains Medis, 2017)
Diarrhea is still potential to grow in Indonesia as a public health problem. In Bali, the prevalence of diarrhea in Jembrana ranks fourth highest. Negara Public Healthcare I have patients with high diarrhea disease. If the distribution of diarrhea cases in 2014 were reported to the Negara Public Healthcare I were analyzed by age group, the most visible cases of diarrhea suffered by a toddler groups, as many as 119 cases or 23% of the total 521 cases were settled in the village Banyubiru Jembrana District of the State. In order to anticipate this public health problem, Negara Public Healthcare I has implemented a range of activities covered by the Environmental Health Program, Disease Eradication Program, and the Community Health Promotion Program.Â The study was conducted in the Village area Banyubiru, District Negara, Jembrana in March-April 2014 using descriptive cross sectional study design with the interview method. The sample in this study were selected through simple random sampling technique. Based on research that has been done, it can be inferred picture characteristics, knowledge, maternal behavior, environment, and the incidence of diarrhea respondents with lower education, children under five suffer from diarrhea in infants in the village Banyubiru